Does response rate of chemotherapy with molecular target agents correlate with the conversion rate and survival in patients with unresectable colorectal liver metastases?: A systematic review. Issue 6 (June 2017) - Okuno, M.; Hatano, E.; Nishino, H.; Seo, S.; Taura, K.; Uemoto, S.
Abstract: Purpose: This study aimed to evaluate whether the response rate of chemotherapy with molecular target agents correlates with the conversion rate, R0 resection rate, and survival in patients with initially unresectable colorectal liver metastases (CRLM). Methods: We reviewed the literature of prospective, controlled trials of systemic chemotherapy for patients with unresectable liver-only CRLM, including resectable extrahepatic metastases. Pearson's correlation coefficients were calculated. Results: A total of 26 patient groups from 18 studies were reviewed. The response rate was significantly correlated with the conversion rate (r = 0.66) and R0 resection rate (r = 0.43) in overall patients. In subgroup analysis, only the conversion rate in patients with chemotherapy only (r = 0.75) and anti-EGFR therapy (r = 0.78) were significantly strongly correlated with the response rate. A non-significant strong trend toward correlation between response and conversion rates was observed in patients with bevacizumab (r = 0.73, p = 0.10). The regression line in the scatter plot of patients using bevacizumab showed a less steep slope. This indicated that conversion rates were relatively less affected by response rates under anti-VEGF therapy compared with the other patient groups. The response rate in chemotherapy-only patients was significantly correlated with median progression-free survival (r = 0.61) and overall survival (r = 0.66). Conclusions: Chemotherapy without molecular target agents and with anti-EGFR agents shows similar results of correlation between response and conversion/R0 resection rates. Under anti-VEGF therapy, conversion would be expected, even with a relatively lower response rate.